Application of Artificial Intelligence in Healthcare Industry: A Critical Review - Ma Cristina, Godala; See, Jason, Toh Seong Kuan; Li, Ming; Lin, Chengzhe (INTI International University, 2024)
Long-term cost-effectiveness studies are needed to determine the financial impact of AI adoption on healthcare systems. Upskilling the healthcare workforce will be vital to ensure professionals can adapt to evolving AI-driven workflows. Developing standardized frameworks will be crucial for seamlessly integrating AI solutions across different healthcare institutions. Beyond the immediate challenges these journals identified, other practical considerations deserve attention. AI in healthcare presents a powerful opportunity for transformation. However, acknowledging and addressing the ethical, practical, and logistical challenges can pave the way for responsible development and ensure AI fulfils its transformative potential, ultimately improving healthcare for all. In conclusion, while AI holds immense promise for the future of healthcare, its successful integration hinges on addressing these critical issues. To translate these findings into practical steps, a multi-pronged approach is necessary. Further research on the effectiveness of AI in various settings and clear regulations are necessary to ensure AI is implemented fairly, ethically, and effectively across the globe.